Rural residents’ willingness to utilize primary care and its influencing factors in the context of graded diagnosis and treatment: a study in Deqing, China - Gao, Meng; Zhu, Xueqing (Frontiers in Public Health, 2024)
BackgroundGraded diagnosis and treatment is a key component in advancing healthcare system reforms and establishing a foundational healthcare framework. Primary care serves as the cornerstone of this system. Understanding the willingness to seek primary care and the factors influencing it can enhance primary care utilization and address the challenges of “difficult access to healthcare” and “high medical costs.”MethodsThis study, based on data from 415 rural residents in Deqing County, Zhejiang Province, analyzes their willingness to seek primary care and the factors influencing it using the Theory of Planned Behavior and structural equation modeling.ResultsThe results of the study show the following: ① Attitude toward behavioral, subjective norm, and perceived behavior control significantly affect willingness to seek primary care, with attitude toward behavior having the greatest influence. ② Regarding attitude toward behavior, residents’ evaluation of treatment costs in primary care, the medical environment, and trust in doctors significantly impact their willingness to seek primary care. ③ In terms of subjective norms, the level of support from others, as well as the recognition of graded diagnosis and treatment systems and family doctor contracting services, positively influence the willingness to use primary care. ④ For perceived behavioral control, residents’ perception of personal and environmental factors affects their willingness to make a first visit to primary care facilities.ConclusionThe study recommends strengthening the awareness of the necessity of primary care among rural residents, improving the experience at the primary level, stimulating the desire for primary care, and increasing the frequency of primary care utilization.